Dialektika Alam dan Manusia dalam Perspektif Geografi Sosial (Sebuah Kajian tentang Interaksi Timbal Balik Lingkungan dan Manusia) - Tue, Febriyani; Lasulika, Cindy Tsasil; Hasim, Hasim; Nurfaika, Nurfaika (Universitas Pahlawan Tuanku Tambusai, 2024)
The relationship between humans and the natural environment is a central theme in social geography, illustrating the reciprocal interaction between humanity and nature. Humans utilize and modify the environment to meet their needs, while the environment influences societal life patterns. This study employs a literature review approach to explore three main aspects: the interaction between humans and nature, the impacts of environmental changes on humans, and environmental management policies. The findings reveal that while humans possess the ability to alter nature, uncontrolled exploitation often leads to environmental degradation, such as pollution, deforestation, and climate change. Conversely, the environment shapes various aspects of human life, including settlement patterns, livelihoods, and culture. Sustainable environmental management policies are essential for achieving harmony between humans and nature. In this context, philosophical thought provides ethical and existential foundations to holistically address environmental challenges, emphasizing human responsibility as an integral part of the ecosystem. Collaborative efforts from various stakeholders are necessary to establish a balance that supports the sustainability of both human and natural life in the future. Keyword: Reciprocal interaction, Natural Environment, Humans